Lipid metabolism and production of incretins in patients with obesity and type 2 diabetes mellitus after biliopancreatic diversion in Hess-Marceau modification at the early stages of follow-up - Ekaterina Ershova; Ekaterina Troshina; Yury Yashkov (Ожирение и метаболизм, 2016)
Objectives: To study the lipid metabolism and secretion of GLP-1 and GIP in obese patients with type 2 diabetes before and 3 months after biliopancreatic diversion (BPD) in Hess-Marceau modification.Materials and methods: 22 patients (44 [38.0; 55.0] years) with morbid obesity (BMI of 50.1 [41.3; 53.8]) and type 2 diabetes were included in the study. Total cholesterol, LDL-C, HDL-C, TG, GLP-1, GIP were evaluated before and 3 months after BPD.Results: At 3 months after BPD there were decreases in weight by 15.8% and a reduction in total cholesterol levels and LDL-C, an increase in the number of patients with a target value of total cholesterol and LDL-C (from 4/22 (18%) to 20/22 (91%, p = 0.0001)). TG levels during the first 3 months after BPD did not change, but there was a trend to an increase in the number of patients with TG target levels (from 8/22 (32%) to 15/22 (68%, p = 0.058)). Due to the reduction of total cholesterol intake after malabsorbtive surgery, we saw a regular decrease in HDL-cholesterol. 3 months after BPD there was an increase in basal secretion of GLP-1 and GIP as compared to preoperative levels, and a strong positive association of the basal GIP with the HDL-C (r = 0,8, p = 0.007) and a strong negative association – with the atherogenic index (r = – 0,7, p = 0.009) at 3 weeks after surgery.Conclusions: The majority of patients with obesity and type 2 diabetes as early as at 3 months after BPD in the modification by Hess-Marceau achieve a significant improvement in the parameters of lipid metabolism; expect positive impact of the GIP on lipid metabolism.